An Inovasi Batik Ecoprint Berbasis Tri-N untuk Meningkatkan Dimensi Kreatif Peserta Didik SD - Purwaningsih, Sri (Tuladha : Jurnal Pendidikan Dasar, 2025)
Sri Purwaningsih, 2022085015: Tri-N Based Ecoprint Batik LKPD Innovation to Increase the Creative Dimension of Elementary School Students. Thesis. Yogyakarta: Basic Education Study Program, Postgraduate Directorate Education, Sarjanawiyata Tamansiswa University. The objectives of this study include (1) producing ecoprint batik LKPD with Tri-N-based characteristics to improve the creative dimension of elementary school students; (2) testing the feasibility of Tri-N-based ecoprint batik LKPD in improving the creative dimension of elementary school students; and (3) testing the effectiveness of Tri-N-based ecoprint batik LKPD in improving the creative dimension of elementary school students. The development research method used in this study is the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model which focuses on the development of innovative and interesting teaching materials. Data collection techniques use interviews, observations, and questionnaires, and documentation. Data analysis techniques in this development research use qualitative and quantitative analysis techniques. The subjects of the limited trial were fourth grade students at SDN 1 Karangpoh with a total of 10 students while the extensive trial was fourth grade students at SDN Jemur with a total of 24 students. The results of this development research are (1) the production of Tri-N-based ecoprint batik LKPD products to improve the creative dimension of elementary school students. Tri-N-Based Ecoprint Batik LKPD teaching materials have niteni, niroake, nambahake activities that can attract students' attention in learning, especially in the implementation of the Pancasila Student Profile Strengthening Project; (2) the results of the product feasibility test meet the very feasible category based on the average validator percentage of 94.44%. Product validation is obtained based on the results of the assessment of the content of the material and teaching material products by two expert lecturers; and (3) the results of the effectiveness test increased from the needs analysis by 23.33% and increased to 85% in the limited trial, and increased again to 91.32% in the broad trial with very creative qualifications. The results of the questionnaire on the developed product showed very good criteria with a percentage of 96.88% for teacher responses and 96.32% for student responses. The N-Gain results of 78% in limited trials and 86% in extensive trials confirm that the developed LKPD is very effective.